Fragilidade ambiental, distribuição espacial de viveiros e estimativa de potencial produtivo da tilápia do Nilo (Oreochromis niloticus) na bacia hidrográfica do Arroio Marreco utilizando SIG - Lira, Karen Carrilho da Silva (2022)
Assessment of environmental fragility in watersheds is an important tool to assist managers in planning and interventions for sustainable production and environmental conservation. The objective of this work was to use Fuzzy logic and the Analytic Hierarchy Process (AHP) method to classify environmental fragility in Marreco River watershed, located in western Paraná. To classify areas, a geographic information system (GIS) and data from a digital elevation model (DEM), as well as data on soil occupation and type were used. The analysis found that 71.3% of the basin area has average fragility. Compared to two other forms of weighing elements of the slope map, the three presented statistical difference, but all indicated that the basin under study mostly has average environmental fragility. The use of Fuzzy logic allowed application of a continuous variation of weights according to the variation of environmental characteristics, which may more effectively represent the reality and, therefore, provide more reliable results. In addition, the growth in tilapia production points to the importance of studies on the best processing of the raw material, aiming at sustainable growth and stimulating the increase in income of warehouse and rural producers in the region. The second objective of this work was to estimate the productive potential of Nile tilapia considering different products (whole fish, fillet, mechanically separated meat (MSM), flour and oil) and to analyze the spatial distribution of the excavated ponds using the Kernel density estimator through a GIS. The results showed that most of the excavated ponds are in areas of average environmental fragility, with a higher density of production located in the Baixo Marreco sub-basin and near the Marreco River and highways, indicating the existence of a logistical structure for the flow of production. And considering the average productivity of 68t/ha/year, the basin has a productive potential of 11,029,60 t per year, representing 57.7% of the total production of the municipalities to which it belongs. In addition, the use of waste can represent an increase of 115.5% in annual gross revenue considering filleted fish, MSM, flour and oil in relation to whole fish. These data indicate a possible increase in revenue for warehouses and producers in the region, taking advantage of the existing water extension and waste from fish processing, contributing to the environment preservation and sustainable growth of the activity.